IMPROVING DESCRIPTIVE WRITING ABILITY OF THE FIRST YEAR STUDENTS OF SMA TOHA PRAKTIKA GILIGENTING-SUMENEP BY USING PICTURES - Rini Yudiati (Faculty of Teaching and Education, University of Wiraraja, 2011)
In Indonesia English is a foreign language, not a second language. As a result, it is very difficult for the students to write a paragraph in English because writing is a complex process that allow writers to explore thoughts and ideas, and make them visible and concrete. The indonesian students’ achievement in writing descriptive paragraph is very low due to several reasons. Firstly, the Indonesian community does not support the existence of the English situation Based on the fact, the researcher focuses this thesis on the problem of improving descriptive writing ability of the first year students of SMA Toha Praktika Giligenting Sumenep by using pictures. The research problem is How can the use of pictures improve the students’ability in writing a descriptive paragraph at SMA Toha Praktika?. The researcher thought that if the students can develop their imagination by the pictures, they will be able to create descriptive paragraphs that are meaningful. To answer the research problem, this research use the classroom action research at SMA Toha Praktika on the first year students academic year 2010/2011 who have difficulties in writing descriptive paragraph. Exercises was done to know how high the students’ ability in writing descriptive paragraph. the data collection involved instruments, namely writing observation, composition test and questionnaires. The composition test was to measure the students’ ability in writing descriptive and questionnaires was to know the students’ opinion about the implementation of pictures. All of the data were analyzed and compared with the criteria of success that the minimun score of the students was 60 and there was 60% or 17 students mastered the material and can made descriptive paragraph.